2011
DOI: 10.3928/01477447-20110427-25
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatic Spinal Epidural Lipomatosis with Severe Obesity at a Young Age

Abstract: Symptomatic spinal epidural lipomatosis is a rare disorder characterized by overgrowth of fat in the extradural space. Most patients have an underlying endocrine disorder, such as Cushing's syndrome, or have taken exogenous steroids chronically. Although less common, obesity alone is thought to be a cause of spinal epidural lipomatosis, representing <25% of reported cases. Patients rarely become symptomatic before middle age without chronic exogenous steroid use. The usual clinical manifestations are similar t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 11 publications
1
12
0
1
Order By: Relevance
“…192 Obese patients are at risk for epidural lipomatosis from epidural injections. 193 Increased adipose tissue can distort the thecal sac and compress neural structures exiting the spinal cord. A review of 70 cases of epidural lipomatosis on magnetic resonance imaging and 34 randomly selected controls showed that the BMI was significantly elevated for the study group and revealed a strong correlation between the number of subsequent epidural corticosteroid injections and new occurrences of epidural lipomatosis.…”
Section: Interventional Pain Management In Obese Patientsmentioning
confidence: 99%
“…192 Obese patients are at risk for epidural lipomatosis from epidural injections. 193 Increased adipose tissue can distort the thecal sac and compress neural structures exiting the spinal cord. A review of 70 cases of epidural lipomatosis on magnetic resonance imaging and 34 randomly selected controls showed that the BMI was significantly elevated for the study group and revealed a strong correlation between the number of subsequent epidural corticosteroid injections and new occurrences of epidural lipomatosis.…”
Section: Interventional Pain Management In Obese Patientsmentioning
confidence: 99%
“…O besity, commonly defined as a body mass index (BMI) of ‡30 kg/m 2 , affects one-third of the adult U.S. population, accounts for 10% of all U.S. health-care expenditures, and is associated with numerous clinical sequelae [1][2][3][4] . The impact of obesity on musculoskeletal and spinal disease, including low back pain, facet arthritis, and degenerative disc disease, has been well documented [5][6][7][8][9][10][11] . Although some studies have reported increased postoperative complications after spine surgery, multiple studies have demonstrated a beneficial effect from surgery on obese patients with the appropriate indications [12][13][14][15] .…”
mentioning
confidence: 99%
“…In previous case reports, SEL was induced in most patients by steroids, obesity, or idiopathic causes [10], [11].…”
Section: Discussionmentioning
confidence: 86%